(untitled) (Journal of Applied Oral Science, 2024)
This retrospective study aimed to analyze the clinical efficacy of two regenerative surgical methods — Bio-Oss granules combined with barrier membranes and Bio-Oss Collagen alone — and to help clinicians achieve better periodontal regeneration outcomes in the specific periodontal condition. Methodology: Patients who underwent periodontal regeneration surgery from January 2018 to April 2022 were retrospectively screened, and their clinical and radiographic outcomes at 6 months postoperatively were analyzed. The probing depth (PD), clinical attachment level (CAL), bleeding on probing (BOP), gingival recession (GR), distance from the cemento-enamel junction to the bottom of the bone defect (CEJ-BD), and depth of intrabony defects (INFRA) were recorded before the operation (T0) and 6 months after it (T1), and subsequently compared. Results: In total, 143 patients were included — 77 were placed in the Bio-Oss group and 66 were placed in the Bio-Oss Collagen group. All indicators, including PD and CAL at T1, showed significant differences compared to baseline, for both groups (P<0.001). PD reduction was greater in the group receiving the Bio-Oss Collagen treatment (P=0.042). Furthermore, in cases when the baseline PD range was 7-11 mm and the age range was 35-50 years, PD reduction was more significant for patients receiving the Bio-Oss Collagen treatment (P=0.031, 0.023). A linear regression analysis indicated that postoperative PD and CAL were positively correlated with baseline values, and that the efficacy tended to decrease with increasing age. Conclusion: Both the use of Bio-Oss Collagen alone and the use of Bio-Oss granules combined with barrier membranes resulted in significant effects in the treatment of periodontal intrabony defects. The Bio-Oss Collagen treatment generated more improvements in PD than the Bio-Oss granules combined with barrier membranes, particularly within the baseline PD range of 7-11 mm and the 35-50 years age group. Additionally, age was the main factor influencing the effectiveness of regenerative surgery for intrabony defects: older individuals exhibited fewer improvements.